“A Study on Talent Management Strategies and Its Impact on Retention of Employees Working in It and ITES Companies in Bangalore During Covid-19 Pandemic” - Vaithyanathan R, A. Narasima Venkatesh (Journal of Informatics Education and Research, 2025)
Introduction: The influence of talent management strategies on employee performance and retention during COVID-19 is the focus of this study. The results of the study demonstrated that employee performance was significantly improved by talent management techniques, including recruiting and selection to draw in talent, coaching and mentoring to foster talent and compensation to retain talent. Literature Review: In order to foster a favourable work atmosphere, establishing specific objectives, as well as offering chances for advancement, talent management strategies may raise employee performance and in turn lead to retention of employees. Methodology: The main quantitative data gathering approach used in this study aids in the statistical analysis of the data gathered. Three demographic questions and seven topic-related questions enable researchers to examine the data gathered through an online survey. Findings: Since researchers can use "descriptive statistics" in SPSS analysis, "regression analysis" and "correlation" tests can also be included in this section. Researchers can determine the correlation between the variables by using this hypothesis testing. In this section, "dependent, and independent variables" are so identified. Discussion: Critical discussion about this research has been highlighted in this section. Therefore, this research section helps to address that “talent management strategies” has a significant impact on the overall performance of the organization. Employee’s performance as well as employee’s retention has to be measured with the aid of this talent management strategies. Conclusion: Covid-19 brought unprecedented challenges to various workplace and requiring organizations to rethink their “talent management strategies". Moreover, effective talent management strategies played a significant role in maintaining employee’s performance and retention of the employees during the Covid-19 pandemic